The Effect of Fresh and Frozen Embryo Transfer on Maternal and Perinatal Results in Pregnancy by Assisted Reproductive Therapy - Ciraci, Tugce; Kapudere, Bilge; Cevrioglu, Arif Serhan; Budak, Ozcan; Bostanci, Mehmet Suhha; Akdemir, Nermin; Ozden, Selcuk (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVES: To investigate the effect of different embryo transfer (ET) methods on maternal and perinatal outcomes in vitro fertilization (IVF) pregnancies after fresh ET and frozen embryo transfer (FET). STUDY DESIGN: The files of 1506 patients who underwent ET between April 2017 and March 2022 were scanned. 136 of 147 patients who gave live birth were included in the study, and two groups were formed according to fresh ET and FET. The groups were compared regarding maternal, fetal, and perinatal outcomes. RESULTS: Fresh ET was performed in 45.3% of the patients, and FET was performed in 54.7%. In the fresh and frozen groups, the biochemical pregnancy positivity rates were 19.21% vs. 17.71%, and the live birth rates were 10.41% vs. 9.22%, respectively. Both were similar, and no significant difference was observed (p=0.457; p=0.721). There was no difference between the fresh ET and FET groups in terms of preterm birth, birth weight, and baby gender. The rate of babies with large gestational age (LGA) was higher in the FET group (p=0.038). Pregnancy-related hypertensive diseases were relatively higher in the FET group (p=0.097). The neonatal intensive care unit (NICU) hospitalization rate was higher in FET cases (p=0.022). CONCLUSION: It was determined that the risks of pregnancy-related hypertensive diseases, LGA fetuses, and hospitalization in the NICU might be higher in pregnancies following FET after endometrial preparation with the hormonal method (HM) in IVF treatment compared to fresh ET pregnancies. Prospective, randomized, controlled research results are needed to evaluate the subject better